Implementasi AHP-WASPAS Untuk Pemilihan Internet Service Provider (ISP) - dirgantara krisna gaesa; Setyawan Wibisono (STEKOM PRESS, 2023)
Internet Service Provider (ISP) is a company that provides internet services. The ISP network is a national and international scale network so that customers can be connected globally. There are many factors that must be considered in selecting an ISP, making choosing an ISP a difficult task. Factors that influence ISP selection include cost, bandwidth, coverage area and type of connection. ISP providers offer a variety of advantages that make it difficult for customers to choose the right provider. The method applied in determining ISP providers is the AHP method used for weighting criteria while the WASPAS method is used for evaluating ISP providers with the criteria of cost, bandwidth, coverage area and type of connection. The rating process using the WASPAS method uses four assessment criteria, namely cost with a weight of 0.54, bandwidth with a weight of 0.38, coverage area with a weight of 0.05 and type of connection with a weight of 0.03. The final results of the ranking show that ISPs with low cost, large bandwidth and wide coverage areas will make these ISPs the best choice, this is because the criteria for cost, bandwidth and coverage area have high weight. Conversely, ISPs with high costs and small coverage areas will be the worst choices in the ranking list.